Respuesta :

Answer:

C

Step-by-step explanation:

[tex]x=2+\sqrt{x-2} \\\\x-2=\sqrt{x-2} \\\\(x-2)^2=\pm(x-2) \\\\x^2-4x+4=\pm(x-2) \\\\[/tex]

[tex]x^2-5x+6=0[/tex] OR [tex]x^2+3x+2=0[/tex]

x=2 and 3

Hope this helps!

Answer:

The answer is option 3.

Step-by-step explanation:

Firstly, we have to move the unrelated term to the other side :

[tex]x = 2 + \sqrt{x - 2} [/tex]

[tex]x - 2 = \sqrt{x - 2} [/tex]

Then, you have to get rid of square root by squaring both sides :

[tex] {(x - 2)}^{2} = {( \sqrt{x - 2} )}^{2} [/tex]

[tex] {x}^{2} - 4x + 2 = x - 2[/tex]

[tex] {x}^{2} - 4x + 4 - x + 2 = 0[/tex]

[tex] {x}^{2} - 5x + 6 = 0[/tex]

Next, you have to solve it :

[tex] {x}^{2} - 5x + 6 = 0[/tex]

[tex] {x}^{2} - 2x - 3x + 6 = 0[/tex]

[tex]x(x - 2) - 3(x - 2) = 0[/tex]

[tex](x - 2)(x - 3) = 0[/tex]

[tex]x - 2 = 0 \\ x = 2[/tex]

[tex]x - 3 = 0 \\ x = 3[/tex]

ACCESS MORE